2023
DOI: 10.1017/s0950268823001206
|View full text |Cite
|
Sign up to set email alerts
|

Legionellosis on the rise: A scoping review of sporadic, community-acquired incidence in the United States

Michelle A. Moffa,
Clare Rock,
Panagis Galiatsatos
et al.

Abstract: Over the past two decades, the incidence of legionellosis has been steadily increasing in the United States though there is noclear explanation for the main factors driving the increase. While legionellosis is the leading cause of waterborne outbreaks in the US, most cases are sporadic and acquired in community settings where the environmental source is never identified. This scoping review aimed to summarise the drivers of infections in the USA and determine the magnitude of impact each potential driver may h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 51 publications
0
1
0
Order By: Relevance
“…Many studies have found that increased precipitation, temperature, and relative humidity are positively associated with the occurrence of LD, particularly a sequence of elevated temperatures followed by a period of increased precipitation, high relative humidity, and low wind [ 28 , 29 ]. The intensification of extreme meteorological events due to climate change (for instance, high temperature variations and heavy rainfall), may create conditions for the development of Legionella and increase the incidence of LD [ 30 , 31 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…Many studies have found that increased precipitation, temperature, and relative humidity are positively associated with the occurrence of LD, particularly a sequence of elevated temperatures followed by a period of increased precipitation, high relative humidity, and low wind [ 28 , 29 ]. The intensification of extreme meteorological events due to climate change (for instance, high temperature variations and heavy rainfall), may create conditions for the development of Legionella and increase the incidence of LD [ 30 , 31 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…Legionellosis, a result of Legionella bacterium infection, involves both LD and the flu-like disease known as Pontiac Fever [5]. LD is an increasingly prevalent atypical pneumonia that is possibly acquired in the community, through travel, or nosocomial infection.…”
Section: Introductionmentioning
confidence: 99%